ON THE ROLE OF THE LITERARY ENVIRONMENT IN SOCIAL LIFE IN EGYPT IN THE LATE 19TH AND EARLY 20TH CENTURIES - Murtazoev , Valijon Kh. (Oriental Journal of Philology, 2025)
This article provides a scholarly analysis of the impact of Egypt's literary environment in the late 19th and early 20th centuries on social life. This period is marked by British colonial rule, national awakening movements, and cultural modernization processes. Literature is examined as a tool for shaping national identity, resisting colonialism, and transforming the socio-political landscape. The study also explores the development of Egyptian journalism, the emergence of modern literary genres, and the rise of feminist literature.